Pembinaan UTBK-SNBT Kategori Penalaran Kuantitatif dan Penalaran Matematika di SMA Kartika XIX-2 Bandung - Aripin, Usman; Rosmiati, Tanti; Gunawan, Guntur (ABJIS: Al-Bahjah Journal of Islamic Community Service, 2024)
SNPMB is the 2023 National Selection for Admission of PTN New Students which was previously called SBMPTN (Joint Selection for State University Entrance). The SNP was formed by the Minister of Education and Culture to prepare for selection to enter PTN. This team is responsible to the Minister of Education, Culture, Research and Technology. The SNPMB test line is called SNBT (Test-Based National Selection). This policy underwent many changes from the previous SBMPTN, namely the basic science and technology ability test was replaced with a literacy test (Indonesian, English, mathematics). dedication This focus discusses the characteristics of the mathematics test both on the Scholastic Knowledge Test and the mathematical literacy test. The purpose of this exercise is to socialize SNBT information and training in dealing with quantitative reasoning and mathematical reasoning questions. The outputs achieved were Quantitative Reasoning and Mathematical Reasoning Question Drafts, draft articles on the results of community service activities. The method used was seminars and training for 30 class XII students of SMA Kartika XIX-2 Bandung. As for the results of the training, all students looked very enthusiastic in participating in coaching, this can be seen from the enthusiasm of students in working on problems with their groups and enthusiasm in asking questions and expressing their opinions, students can solve questions after getting a strategy for working on questions by the instructor.